International Tourism Demand in Indonesia: Gravity Model Approach - Nahar, Faiza Husnayeni; Adha, Mufti Alam; Azizurrohman, Muhammad; Ulfi, Izzani; Karimah, Husna (JEJAK: Jurnal Ekonomi dan Kebijakan, 2019)
Tourism is considered as big industry which growing up faster compare to other industry in this recent year. It is reported that Indonesia received approximately 11.5 million of international tourists in 2016. Because the tourism shows significant trend in Indonesia and getting strong position in the third rank as the foreign revenue for this country, the government willing to boost up the factors that might contribute more on attracting international tourist. This study tried to analyse the determinant factors of international tourist in Indonesia by using Random Effect Model. The variables are GDPs origin and destination country, exchange rate of origin country, free visa impact and length of distance in Indonesia during the period of 2006 to 2016. The study found that all variables are statistically significant. GDPs origin and destination country and country with visa-free entry have positive effect to the number of international tourist arrival while the rest which is exchange rate of origin country and length of distance have negative effect to the international tourists. Hence, the government needs to promote aggressively to the international tourist by conducting important events, increasing the number of countries that receive Indonesia free visa and maintain the GDP in both origin and destination country.